"GENDER STRUCTURE" (BIBLICAL PERSPECTIVE ON GENDER EQUALITY) - Yusak Setianto (Phronesis: Jurnal Teologi dan Misi, 2022)
The issue of Gender does not yet have a common ground. Women are always considered weak and helpless human beings. However, in some ethnic groups in Indonesia, the opposite is true. Men are deemed to have no value to women. This study aims to examine the concept of gender equality from a biblical perspective. As the primary source of teaching authority, the Bible provides a solid picture of gender equality. The research method used is exploratory qualitative. The results of the study state that the Bible consistently discusses the principle of gender equality. Because gender equality is essential, many activists voice this principle in the struggle for human rights. Therefore, viewing humans as the noblest created beings is the basis for this struggle for gender equality. Thus, opportunities and responsibilities in all aspects of life own by all humans and created by God.